2013
DOI: 10.1111/eff.12075
|View full text |Cite
|
Sign up to set email alerts
|

Nursery sources and cohort strength of young‐of‐the‐year common carp (Cyprinus carpio) under differing flow regimes in a regulated floodplain river

Abstract: Otolith chemistry and standardised catch data were used to identify key nursery sources for common carp (Cyprinus carpio) in the mid-Murray River region, south-east Australia, and to quantify annual young-of-theyear (YOY) cohort strength under varying hydrological conditions across 4 years (2005/2006-2008/2009). Analysis of trace element concentrations (i.e., Mg:Ca, Mn:Ca, Sr:Ca, Ba:Ca) near the otolith core of post-larval carp (< 1 month of age) resulted in moderate to very high spatial discrimination of nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Rather, the misclassification of individuals to distant locations appears to be due to the high number of locations relative to the limited number of elements that contributed to location separation in the discriminant function analysis. Similar overlap and misclassification in otolith chemical signatures among locations have been reported previously both in freshwater (e.g.,Macdonald & Crook, 2014) and marine (e.g.,Miller, Banks, Gomez-Uchida, & Shanks, 2005) studies.…”
mentioning
confidence: 99%
“…Rather, the misclassification of individuals to distant locations appears to be due to the high number of locations relative to the limited number of elements that contributed to location separation in the discriminant function analysis. Similar overlap and misclassification in otolith chemical signatures among locations have been reported previously both in freshwater (e.g.,Macdonald & Crook, 2014) and marine (e.g.,Miller, Banks, Gomez-Uchida, & Shanks, 2005) studies.…”
mentioning
confidence: 99%
“…Subsequently, the existence of inter-annual variability in chemical signatures associated with specific nursery grounds was identified, showing that precise determination of production hotspots-either based on capture sites or habitat types-was plausible following the formulation of an annual baseline database of location-specific chemical signatures (Macdonald et al 2010;Crook et al 2013). Ultimately, Macdonald and Crook (2014) demonstrated that the use of an annual baseline database provided a significant improvement of classification power of post-larvae origin to their nurseries (53 to 70% of correct classification). Admittedly, the classification procedure was not without error but could provide data sufficiently precise for management applications (e.g.…”
Section: Common Carp Management In Australia and Classification Perfo...mentioning
confidence: 99%
“…Vilizzi and Walker 1995). Thus, studies have used either the 'larger' asterisci (Crook and Gillanders 2006;Blair 2008;Li et al 2011;Blair and Hicks 2012) or the lapilli (Macdonald et al 2010;Crook et al 2013;Macdonald and Crook 2014), even though remarkable differences in microchemistry have been observed between the two pairs, suggesting the need for their concomitant employment (Macdonald et al 2012).…”
Section: Otolithmentioning
confidence: 99%